The Dominant Role of Intrinsic Motivation and Extrinsic Motivation in Improving the Performance of Gymnasts - Dendi Wiranata; Helmy Firmansyah; Alit Rahmat (Journal of Physical Education Health and Sport, 2026)
Athlete performance in gymnastics is influenced by various psychological factors, particularly motivation, which plays a crucial role in training consistency and competitive outcomes; however, previous studies have shown inconsistent findings regarding whether intrinsic or extrinsic motivation has a more dominant influence, especially among student-athletes in structured training programs. Therefore, this study aims to analyze the role of intrinsic and extrinsic motivation in improving the performance of gymnastics athletes and to determine the most dominant motivational factor. This study employs a quantitative approach with a correlational method, involving 11 gymnastics athletes who are members of the Student Education and Training Center (PPLP) program selected using a total sampling technique. Data were collected through Likert-scale questionnaires using the Sport Motivation Scale II (SMS-II) to measure intrinsic and extrinsic motivation and the Test of Performance Strategies (TOPS) to assess athlete performance. Data analysis was conducted using Pearson correlation and multiple linear regression with the assistance of SPSS. The results indicate that intrinsic motivation does not have a significant effect on athlete performance, as evidenced by a t-value of 0.831 and a significance level of 0.430 (>0.05), whereas extrinsic motivation has a significant effect with a t-value of 3.594 and a significance level of 0.007 (<0.05), and emerges as the most dominant variable with a beta coefficient of 0.962. Simultaneously, intrinsic and extrinsic motivation significantly influence athlete performance (F = 8.770; p = 0.010 < 0.05), while the coefficient of determination (R Square) of 0.687 indicates that 68.7% of the variation in athlete performance is explained by these variables, confirming that extrinsic motivation plays a more dominant role in this context.